2017
DOI: 10.1167/iovs.16-20998
|View full text |Cite
|
Sign up to set email alerts
|

Monocarboxylate Transporters Mediate Fluorescein Uptake in Corneal Epithelial Cells

Abstract: PURPOSE.To determine the presence of monocarboxylate transporter (MCT) in human and rabbit corneal epithelium and its role in transcellular fluorescein transportation in the cornea. METHODS.The presence of MCTs in human and rabbit corneal epithelium was determined by RT-PCR and immunohistochemistry. Intracellular fluorescein uptake experiment was performed using cultured human corneal epithelial cells (HCECs). The involvement of MCT in fluorescein uptake was determined by addition of MCT inhibitors to HCECs an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“… 15 , 16 Recent studies favor the idea that fluorescein stains individual cells, particularly those with altered physiological conditions. 14 , 17 , 26 Adhering to this idea, our study found that fluorescein ingress was reduced in HCECs that had been promoted to express MUC1, whereas a knockdown of MUC1 in HCECs enhanced fluorescein ingress. This effect was likely attributed to the MUC1 extracellular domain because overexpressing MUC1-C (the MUC1 cytoplasmic domain) failed to decrease fluorescein ingress in HCECs.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“… 15 , 16 Recent studies favor the idea that fluorescein stains individual cells, particularly those with altered physiological conditions. 14 , 17 , 26 Adhering to this idea, our study found that fluorescein ingress was reduced in HCECs that had been promoted to express MUC1, whereas a knockdown of MUC1 in HCECs enhanced fluorescein ingress. This effect was likely attributed to the MUC1 extracellular domain because overexpressing MUC1-C (the MUC1 cytoplasmic domain) failed to decrease fluorescein ingress in HCECs.…”
Section: Discussionmentioning
confidence: 57%
“… 14 16 Nonetheless, our previous study has shown that fluorescein ingress into the corneal epithelial cells can also occur through the monocarboxylate transporter. 17 Herein, we used both in vivo and in vitro approaches to examine whether the expression of transmembrane MUC1 is causally linked to blocking of fluorescein ingress through corneal epithelial cells as another working mechanism to explain how fluorescein punctate staining might develop in dry eye diseases.…”
mentioning
confidence: 99%
“…In our transcriptomic analysis, we observed a significant upregulation in the expression of SLC16A7 gene, which encode monocarboxylate transporter 2 and has an affinity for acetoacetate and their derivatives metabolites (methyl-2-oxovaleric acid and 3-methyl-2-oxobutanoic) 28 . Considering the domination of the monocarboxylate transporters on the apical direction of the corneal epithelium 29 , DCF might have an active impact of these transporters, leading to the excessive transportation of these metabolites in the apical direction. However, the precise mechanism favoring their apical release under DCF remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…In the human cornea, to date, MCTs are critically understudied with only eleven studies published [ 4 7 , 12 , 17 22 ]. The majority of the existing literature focus on the expression of MCTs 1-4 [ 12 , 18 , 21 ] and MCT5 [ 19 ], as they relate to the corneal epithelium. Corneal endothelial cells have also been reported to express MCT1, MCT4, and MCT8 [ 17 , 22 ].…”
Section: Introductionmentioning
confidence: 99%